Update on Family Psychoeducation for Schizophrenia - Lisa B. Dixon; Curtis B. Adams; Alicia Lucksted (2000)
The Schizophrenia Patient Outcomes Research Team and others have previously included family psychoeducation and family support in best practices guidelines and treatment recommendations for persons with schizophrenia. In this article we review in detail 15 new studies on family interventions to consider issues around the implementation of family interventions in current practice. The data supporting the efficacy of family psychoeducation remain compelling. Such programs should remain as part of best practices guidelines and treatment recommendations. However, assessment of the appropriateness of family psychoeducation for a particular patient and family should consider (1) the interest of the family and patient; (2) the extent and quality of family and patient involvement; (3) the presence of patient outcomes that clinicians, family members, and patients can identify as goals; and (4) whether the patient and family would choose family psychoeducation instead of alternatives available in the agency to achieve outcomes identified.